The Study of Learning Achievement in English Reading Comprehension by Using KWL-Plus Technique for Sixth Grade Students - Pengmarerng, Sukanya; Pongpisanu, Sudaporn; Boonkusol, Thongpan (Saengtham College Journal, 2026)
The purposes of this study were 1) to compare the Sixth Grade students’ English reading comprehension achievement before and after using KWL-Plus technique, 2) to study the Sixth Grade students’satisfaction towards KWL-Plus technique in English reading comprehension. The research sample group was the Sixth Grade students of Theppitakpittaya School, in the second semester of the 2022 academic year, which consisted of 37 students by cluster sampling. The instruments used for this study included: (1) 5 conventional teaching lesson plans by KWL-Plus with English reading comprehension (2) The academic achievement test in English reading comprehension achievement (3) 15 items of questionnaire with a 5-point scale. The data were analyzed using the mean, standard deviation, and t-test statistics. The research findings were as follows: (1) English reading comprehension achievement after learning was higher than before the treatment at the .05 level of significance; (2) the students’ satisfaction who learned by using KWL-Plus in English reading comprehension was at a high level ( =4.54, S.D.=0.93).